The effects of group free improvisation instruction on improvisation achievement and improvisation confidence. (2nd April 2016) - Hickey, Maud; Ankney, Kimberly; Healy, Daniel; Gallo, Donna
Abstract : While improvisation in K-12 schools in the USA has gained some traction since the inception of the US National Standards in 1994, there is still a dearth of improvisation activities in schools because of the lack of music teacher preparation in improvisation. The purpose of this study was to determine if providing group free improvisation instruction and activities to collegiate non-music majors would help them become better and more confident improvisers. An additional purpose was to examine the relationship between improvisation achievement and selected variables. A repeated measures design was utilised to test improvisation achievement through solo improvisations of college non-music majors enrolled in a free improvisation class. There was no statistical difference in improvisation achievement by time of solo recording; however, improvisation confidence improved over time. Improvisation confidence was correlated with risk-taking personality as well as a pretest self-assessment of improvisation comfort. The findings are discussed in relation to improving improvisation confidence among future music teachers in order to expand more improvisation activities in US K-12 schools.